Variation in Grain Zinc and Iron Concentrations, Grain Yield and Associated Traits of Biofortified Bread Wheat Genotypes in Nepal - Thapa, Dhruba Bahadur; Subedi, Mahesh; Yadav, Rajendra Prasad; Joshi, Bishnu Prasad; Adhikari, Bhim Nath; Shrestha, Keshav Prasad; Magar, Prem Bahadur; Pant, Khem Raj; Gurung, Suk Bahadur; Ghimire, Sapana; Gautam, Nutan Raj; Acharya, Nav Raj; et al. (Frontiers in Plant Science, 2022)
To select high yielding genotypes with elevated grain zinc and iron content, the sixth, seventh, eighth and ninth HarvestPlus Yield Trials (HPYTs) were conducted at three to five locations in Nepal, namely Doti, Surkhet, Bhairahawa, Nepalganj, Khumaltar and Kabre, during four consecutive years: 2015-16, 2016-17, 2017-18 and 2018-19, using 47 biofortified and 3 non-biofortified CIMMYT-bred bread wheat genotypes: Baj#1, Kachu#1 and WK1204 (local check). Genotypic and spatial variations were found in agro-morphological traits, grain yield and its components; and the grain zinc and iron content of tested genotypes. Grain zinc content was highest in Khumaltar and lowest in Kabre. Likewise, grain iron content was highest in Doti and lowest in Surkhet. Most of the biofortified genotypes were superior for grain yield and for grain zinc and iron content to the non-biofortified checks. Combined analyses across environments showed moderately to high heritability for both Zn (0.48-0.81) and Fe (0.46 to 0.79) except a low heritability for Fe observed for 7th HPYT(0.15). Grain yield was positively correlated with number of tillers per m2, while negatively correlated with days to heading and maturity, grain iron, grain weight per spike, and thousand grain weight. The grain zinc and iron content were positively correlated suggesting that the simultaneous improvement of both micronutrients is possible through wheat breeding.